Density and Strength of Foamed Concrete: The Influence on Dynamic Characteristics of Lightweight Profiled Composite Slabs - Rum, Rahmat Hidayat Mohammed; Norhalim, Arnie Farhana; Jaini, Zainorizuan Mohd; Abd Ghafar, Nor Hayati; Kowlowski, Marcin (International Journal of Integrated Engineering, 2019)
This paper presents the experimental study on dynamic characteristics of lightweight profiled composite slabs. The density and strength of foamed concrete as topping material become the subject of interest. This type of floor system offers sustainable and reliable structural component in term of lightness, efficient construction processes and precast element. Although lightweight profiled composite slab may not new thing in construction industry, the understand on dynamic characteristics in term of natural frequency, damping ratio and mode shape are still ambiguous. Lightweight composite slabs made of foamed concrete and Peva45 steel corrugated deck were fabricated with size of 840 mm width, 1800 mm length and 125 mm thickness. The density of foamed concrete is varied at 1400 kg/m3, 1600 kg/m3 and 1800 kg/m3. The cube test revealed that the compression strength of foamed concrete is 15.43 MPa, 22.97 MPa and 32.23 MPa for density 1400 kg/m3, 1600 kg/m3 and 1800 kg/m3 respectively. The natural frequency was observed to decrease with the increment of density and strength of foamed concrete. The natural frequency of lightweight composite slabs is around 30Hz to 35Hz. Meanwhile, the damping ratio is considered quite high at the range of 3% to 5%, where low density of foamed concrete gave more advantage in dissipating vibration within short period. The mode shape was visually obtained using MEScope and represents the bending behaviour.